2022
DOI: 10.1038/s41598-021-03926-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of human mobility to predict regional excess death in Ecuador

Abstract: COVID-19 outbreaks have had high mortality in low- and middle-income countries such as Ecuador. Human mobility is an important factor influencing the spread of diseases possibly leading to a high burden of disease at the country level. Drastic control measures, such as complete lockdown, are effective epidemic controls, yet in practice one hopes that a partial shutdown would suffice. It is an open problem to determine how much mobility can be allowed while controlling an outbreak. In this paper, we use statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…While the fear of infection and of serious health complications has gripped the state of mind of many segments of human societies, lockdown and confinement measures adopted by governments during the COVID-19 pandemic may have tangibly influenced travel patterns of people. A number of empirical studies have investigated and compared the movement of people before, during, and after the lockdown regimes to understand the impacts of NPIs on travel patterns [ 15 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the fear of infection and of serious health complications has gripped the state of mind of many segments of human societies, lockdown and confinement measures adopted by governments during the COVID-19 pandemic may have tangibly influenced travel patterns of people. A number of empirical studies have investigated and compared the movement of people before, during, and after the lockdown regimes to understand the impacts of NPIs on travel patterns [ 15 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At a national scale, several studies found that mobility reduction generally implies a restrain on infections [ 59 , 140 , 141 ]. A positive correlation between mobility and excess mortality was also found in Italy [ 23 ] and Ecuador [ 142 ].…”
Section: Resultsmentioning
confidence: 85%
“…Several studies 7,39,40 found evidence that local, short-range mobility worked as a key modulator of COVID-19 spread. We therefore produce province-level mobility curves based on Google's "Grocery & Pharmacy" and "Workplace" indexes -which express percentage changes in mobility linked to these categories with respect to a pre-pandemic reference (the first five weeks of 2020; see Section 2.3).…”
Section: Mobility Patternsmentioning
confidence: 99%